STRATEGI MANAJEMEN KELAS DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VI DI SD NEGERI TIDUNG - Humaira, Andi Ade Syalwa; Nur, Dina Ulfa; Kalsum, Ummu; Usman, Zubaidah; Hasan, Mardhiah (Department of Islamic Education Management, 2026)
This This study aims to analyze the classroom management strategies implemented by sixth-grade teachers at Tidung State Elementary School and describe their impact on student learning motivation. Classroom management is an important aspect in creating a conducive, orderly, and enjoyable learning environment that can encourage active student involvement in the learning process. This study uses a qualitative approach with a case study design. Data sources were obtained from sixth-grade teachers as primary informants and students as supporting informants through observation techniques, in-depth interviews, and documentation studies. The results of the study indicate that teachers implement participatory, adaptive, communicative, and humanistic classroom management strategies. These strategies are realized through student involvement in spatial arrangement and the preparation of classroom rules, the application of a variety of learning methods, providing positive reinforcement, the use of simple learning media, and building effective two-way communication. This study concludes that the implementation of effective and contextual classroom management plays an important role in increasing the learning motivation of elementary school students, especially in sixth grade.